Civil liberties - 20160731 frey50; Merino, Noel
This book is a collection of articles in which authors debate whether limits should be placed on freedom of expression, whether the First Amendment requires separation of church and state, and whether the right to due process is in danger.
Should limits be placed on freedom of expression? -- Hate speech should be criminalized / Joyce Arthur -- Censorship as "tolerance" / Jacob Mchangama -- Citizens United and the battle for free speech in America / Steve Simpson -- The First Amendment does not protect corporate spending on political speech / Jeffrey D. Clements -- Freedom of speech can't be unlimited / Yasmin Alibhai-Brown -- Attempts to limit free speech online can lead to repressive solutions / Wendy Kaminer -- Does the First Amendment require separation of church and state? -- The First Amendment requires separation of church and state / Garrett Epps -- The First Amendment protects religious expression unless it is coercive / Antony Barone Kolenc -- Schools must protect students from religious indoctrination while allowing religious expression / Martha McCarthy -- Schools should teach about religion / Jeff Passe and Lara Willox -- Anti-religious speech police in America / Newt Gingrich -- Government neutrality on religion is not antireligion / David Niose -- Is the right to due process in danger? -- The military should be allowed to detain noncitizen terrorist suspects / Charles D. Stimson -- The military should not be allowed indefinite detention of terrorist suspects / Glenn Greenwald -- Illegal aliens are granted excessive due process rights / W.D. Reasoner -- Lawless courts / Jacqueline Stevens -- Is the right to privacy in jeopardy? -- All hail Samuel Alito, privacy champion extraordinaire! / Jeffrey Rosen -- The Supreme Court's recent decision in the privacy case US v. Jones does not go far enough / John W. Whitehead -- Security requires that civil liberties, including privacy, not be absolute / Elise Cooper -- Surveillance can't make us secure / Julian Sanchez -- New legislation is needed to protect privacy on the Internet / The Obama Administration -- New legislation is not needed to protect privacy on the Internet / John Stephenson.
Keywords: Civil rights -- United States; Civil rights -- United States; Civil rights; United States; Juvenile works